An assessment of information audit: with special reference to medical library of University Colombo - Ravikumar, Muthurajah Norman (My University, 2010)
In today's fast-paced information business world, success is so often a function of how effectively and quickly a library can employ one of its greatest assets, the information. Especially the medical libraries have become ever so complex when one considers the rapid growth of knowledge in the field of medicine. Also, the parent organizations of these libraries spend a large amount of money for their library activities, thus; these libraries need to adopt new methods to manage the large quantity of available medical literature in an effective manner. A valuable tool in this information management review process is the 'Information Audit'. Information audit is a process which effectively determines the current information environment by identifying what information exists within the organization, where it resides, who uses it and to what effect. Additionally, it provides the opportunity to understand the information requirements of individuals and provides an 'information map' which can be used as a basis for an improved understanding of the information flow. The Medical Library of University of Colombo, is one of the key library which provides medical information for the students, postgraduates, academics and medical professionals in the field of medicine in Sri Lanka. This research study was planned to conduct an information audit at Medical Library of University of Colombo, using Henczels' (2001) seven stage information audit model to achieve the following objectives; . To identify the information needs of the users and assign a level of strategic importance to those needs. . To identify the resources and services currently provided to meet those needs. To map the information flow within the library . . To analyze gaps and inefficiencies that enables the identification of where changes are necessary. Samples of the study consisted academics staff members, post-graduates, undergraduates and library staff of Medical Faculty of UC which amounted to 312. Self- administrated questionnaires and in-house statistics were used as research instruments to collect the data. The study received the response rate of 69.87%. 11 The information audit was focused on three different aspects such as information usage audit, information need analysis audit and information assessment audit. The outcome of the information audit was as follows; Majority of users used the library daily but the usage of academics was low. Most of the users visit the library to borrow and read books. Out of the available library materials, Text books are the highly used resource by the users; especially by the undergraduates. Also, users heavily used print sourceswhile the usage of electronic sources was low. Quantity and quality of available print materials (regarding subject coverage) in library are adequate for students to perform their task but it is inadequate for academics and researchers. Quantity and quality of electronic materials are inadequate to majority of users. Especially quality of CD ROMs, AV materials are low. Moreover, it was found that quantity and quality of available library resources positively affects the frequency of library visits and the usage of library resources. Users are satisfied on most of the service and facilities provided by the library except ILL, Computer assisted search service, Internet facilities, User Education Programmes and Knowledge of library staff. Difficulties encountered in information accessing included lack of time and inadequacy of resources. Majority of library staff expressed that the finance/ budget short falls were the major barriers in improving the library information services. Display of new books at the entrance, introduction of electronic document delivery services, bar-coding of books, MEDLINE facilities and adequate access to information were observed improvements by the users. Users suggested that the library should focus on the enhancement of collections and equipments to cater the new demands. In-addition, conducting user education programmes using new technology; adding latest reference books; subscribing more e-joumals; increasing internet facilities; providing access to e-resources for users from their own desktops; enhancing resources and services of the library, enhanced training programmes for staff and strengthening work force of the library, are recommendations for improvements of the library, in future